2017
DOI: 10.1002/pmh.1382
|View full text |Cite
|
Sign up to set email alerts
|

The Work and Social Adjustment Scale: Psychometric properties and validity among males and females, and outpatients with and without personality disorders

Abstract: The Work and Social Adjustment Scale (WSAS) is an outcome measure assessing degree of functional impairment. Its psychometric properties, validity and sensitivity to change have been supported in several studies. However, no explicit psychometric or validity study of WSAS has been performed on data from a large sample of psychiatric outpatients, with and without personality disorders. The aim of this study was therefore to provide additional knowledge of the properties of WSAS in such a sample. The material co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 56 publications
(118 reference statements)
9
52
1
Order By: Relevance
“…In the current study, the mean GAF score was 49.77 (SD = 6.06), and according to APA [35] within the "Sever" range. Mean WSAS score was 22.60 (SD = 8.56), and according to Mataix-Cols and colleagues [40] and Pedersen and colleagues [41] in the "Moderate" range. In addition, the GSI was 1.54 (SD = 0.66) and IIP was 1.65 (SD = 0.52).…”
Section: Patientsmentioning
confidence: 85%
“…In the current study, the mean GAF score was 49.77 (SD = 6.06), and according to APA [35] within the "Sever" range. Mean WSAS score was 22.60 (SD = 8.56), and according to Mataix-Cols and colleagues [40] and Pedersen and colleagues [41] in the "Moderate" range. In addition, the GSI was 1.54 (SD = 0.66) and IIP was 1.65 (SD = 0.52).…”
Section: Patientsmentioning
confidence: 85%
“…Quality of life was measured with a single question from the WHO-QoL questionnaire: "How would you rate your quality of life on a 5-point Likert scale" [19]. Work and social adjustment were assessed using the Work and Social Adjustment Scale (score range 0-40, with 0 reflecting best adjustment) [20]. Patients were also asked to report their working status and whether they received benefits for health-related reasons by means of several multiple-choice questions.…”
Section: Physical Functioning Quality Of Life Occupational and Socimentioning
confidence: 99%
“…Also, global measures of symptomatology and social functioning were not included in the study. However, previous research has suggested that depression and interpersonal problems are consistent predictors of work and social adjustment (e.g., Pedersen et al, 2017 ). The sample size in the study ( N = 39) restricted the use of more sophisticated statistical procedures due to lack of statistical strength.…”
Section: Discussionmentioning
confidence: 93%